Brachytherapy as an Adjuvant for Recurrent Atypical and Malignant Meningiomas. Issue 5 (24th April 2019) - Koch, Matthew J; Agarwalla, Pankaj K; Royce, Trevor J; Shih, Helen A; Oh, Kevin; Niemierko, Andrezj; Mauceri, Thomas C; Curry, William T; Barker, Frederick G; Loeffler, Jay S
Abstract: BACKGROUND: Recurrent atypical and malignant meningiomas have poor outcomes with surgical therapy alone. Neither adjuvant chemotherapy nor postoperative radiation therapy remedies this problem. OBJECTIVE: To evaluate our experience with the treatment of 15 patients treated with I-125 or Cs-131 brachytherapy radiation seeds as an adjuvant in these difficult cases. METHODS: Patients with high-grade recurrent meningioma who underwent resection and intraoperative placement of brachytherapy seeds at our institution from 2002 to 2014 were identified and studied by retrospective chart review. RESULTS: Fifteen patients with median age of 68.8 yr were treated with I-125 (n = 13) or Cs-131 (n = 2) brachytherapy seeds for cases of recurrent, grade II (n = 8), or grade III (n = 7) meningioma at our institution from 2002 to 2014. These lesions originated from a variety of locations including, convexity (3), falcine (3), frontal (2), occipital (1), parietal (2), 2 sphenoid wing (2), and temporal (2), based recurrent meningiomas. Patients had a median of 2 prior open surgical interventions and received local radiation therapy with a median dose of 55 Gy prior to brachytherapy. Survival at 2.5 yr was 56% for grade II and 17% for grade III lesions. Survival was significantly associated with patient age but not tumoral pathology. Forty percent of patients required reoperations for wound complications following brachytherapy. CONCLUSION: Brachytherapy with implantation of permanent radiation seeds provides a viable alternative treatment for recurrent meningioma while carrying a significant clinical risk of wound infection and need for reoperation. Graphical Abstract: